Perfil das intoxicações por agentes químicos em adolescentes notificadas ao CIT-Belém, de março de 1998 a março de 2006 - FONSECA, Carla de Aviz (2023)
Introduction: Adolescence, the period between childhood and the adult age, is distinguished for the high morbidity and mortality rates by external causes. The poisonings are extremely heterogeneous events of the clinical and epidemiologist point of view. They are defined as a nocious events induced by substances, and it's previsible reply and dose-dependent. Objective: To describe adolescent's chemical poisoning that had been informed to the CIT Belém. Method: Observational and descriptive serial cases study of adolescent's (10 to 19 years, according to WHO) exposures registered in the database of the CIT-Belém, in a period from March of 1998 to March of 2006. The venomous animals, biological toxins and plants had been excluded. The analysis was performed in the program Epi-Info version 6.04b and the table's presentation in OpenOffice.org Calc 2.2.0. Results: 491 cases had been notified (5.55% of the total of cases of the CIT-Belém). Late adolescence (10-14 years) corresponded to 71.3% and the feminine sex 68.8%. Of the occurrences, 89.6% had been poisonings. The suicide attempt counted on 44.6% of all cases, being 51.14% in the late adolescence. In the early one (15-19 years), the individual accidents were 42.5%. Medicines, rodenticides and cleaning substances (household) had been responsible for 36.0% (36.2%: early; 36.0%: late), 30.5% (26,2%: early; 32,2%: late) and 10.4% (17.0%: early; 7.7%: late) of the total of cases, respectively. (60.1%). Conclusion: The emotional and cognitive evolution, probably diminishes the typical accidental poisonings of the pediatric age, and ripens the conception of death, becoming it a possible escape for the adolescent's problems.